Pelatihan Pembuatan Produk Dari Bawang Merah Dengan Kelompok Ibu-Ibu Ceria di Desa Simangulampe - Batubara, Ridwanti; Affandi, Oding; Endah Nurhidayah, Rika; Fauzia Dewinta, Astrid; Ulfa, Mariah (JDISTIRA - Jurnal Pengabdian Inovasi dan Teknologi Kepada Masyarakat, 2024)
One of the local potentials of Simangulampe village, Bakara sub-district, is shallots. The purpose of the PPM (Community Service) activity carried out is to train the community, in this case the Ceria mothers group of Simangulampe Village in making products from processed shallots. The method of this training activity is direct practice followed by material explanation, discussion in the form of questions and answers. Training participants were given the opportunity to respond and comment on the stages of training activities, procedures and training results. The products of the training are fried shallots, flavored fried shallots, and onion oil. At each stage, the process of making the product will determine the final result and the habit of practicing making products frequently will provide better quality results. It is expected that after the training, the Ceria mothers group in Simangulampe Village will continue the shallot production activities and market the shallot products